Framework Development for Clinical Comprehensive Evaluation of Drugs–a Study Protocol Using the Delphi Method and Analytic Hierarchy Process - Zhang, Chi; Ma, Er-Li; Liu, Bing-Long; Wu, Bin; Gu, Zhi-Chun; Lin, Hou-Wen (Frontiers in Pharmacology, 2022)
Measuring the value of drugs to help make health-care decisions is a complex process which involves confronting trade-offs among multiple objectives. Although guidelines have been released for clinical comprehensive evaluation of drugs, refinement is required when considering a specific drug used in a specific disease. In this study, a two-level framework for clinical comprehensive evaluation of drugs will be developed. Six first-level indicators, including safety, efficacy, costs/cost-effectiveness, novelty, suitability, and accessibility will be evaluated according to the Chinese Guideline for Clinical Comprehensive Evaluation of Drugs. The second-level components involved in the framework will be first validated by the Delphi method and subsequently compared with one another to get the index weight based on the Analytic Hierarchy Process (AHP). The scoring criteria of each component in the framework will also be determined by the Delphi method and AHP. The scoring criteria of components representing therapeutic effects will involve both score of therapeutic effects and score of evidence level. With the evidence of the drug to be evaluated, the score of each component will be obtained according to the established scoring criteria, and the overall comprehensive score value of the drug will be calculated, which will assist the evidence-based decision making.